2018
DOI: 10.1016/j.medengphy.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrohysterographic characterization of the uterine myoelectrical response to labor induction drugs

Abstract: Labor induction is a common practice to promote uterine contractions and labor onset. Uterine electrohysterogram (EHG) has proved its suitability for characterizing the uterus electrophysiological condition in women with spontaneous labor. The aim of this study was to characterize and compare uterine myoelectrical activity during the first 4 h in response to labor induction drugs, Misoprostol (G1) and Dinoprostone (G2), by analyzing the differences between women who achieved active phase of labor and those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The reliable prediction of whether an induction agent could trigger APL or not would help clinicians to reduce unnecessary waits and decide whether or not to perform a cesarean section. Benalcazar et al found a significantly different response between the EHG characteristics of patients that succeeded in achieving APL and those that did not [15,16]. In the present work, we performed APL predictor systems (Scenario 1) with different sets of features: obstetrical (PS1_ 1), EHG (PS1_2), and a combination of both (PS1_3).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The reliable prediction of whether an induction agent could trigger APL or not would help clinicians to reduce unnecessary waits and decide whether or not to perform a cesarean section. Benalcazar et al found a significantly different response between the EHG characteristics of patients that succeeded in achieving APL and those that did not [15,16]. In the present work, we performed APL predictor systems (Scenario 1) with different sets of features: obstetrical (PS1_ 1), EHG (PS1_2), and a combination of both (PS1_3).…”
Section: Discussionmentioning
confidence: 97%
“…In a previous work, to analyze the evolution of the EHG burst parameters in response to labor induction drugs, we first computed the median values of each parameter associated with the EHG bursts present in nonoverlapping intervals of 30 minutes [15,16]. Results showed that for successful inductions, statistically significant and sustained increases with respect to the basal period were obtained after 60 minutes and 120 minutes in patients induced with misoprostol and dinoprostone, respectively [15,16]. This is the reason why, in the present work, in order to use only the significant intervals for both drugs, for each parameter, we analyzed 5 intervals of 30 minutes (basal period-before drug administration: 120 ′ , 150 ′ , 180 ′ , and 210 ′ ), giving rise to a total of 21 × 5 = 105 EHG features.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations